KIR and Human Leukocyte Antigen Genotype Associated Risk of Cytomegalovirus Disease in Renal Transplant Patients. Issue 7 (July 2015) - Michelo, Clive M.; van der Meer, Arnold; Tijssen, Henk J.; Zomer, Ramona; Stelma, Foekje; Hilbrands, Luuk B.; Joosten, Irma
<x xml:space="preserve">Abstract</x> Background Cytomegalovirus(CMV) infections have a significant effect on morbidity and mortality in kidney transplants. We conducted a study to ascertain the association of natural killer cell killer immunoglobulin-like receptors and human leukocyte antigen (HLA) genotype with risk of CMV disease. Methods The 90 CMV-negative patients receiving a first renal transplantation from a CMV-positive donor in this study received triple immunosuppressive therapy and prophylactic CMV treatment for up to 3 months after transplantation. Results We observed a 43.3% incidence rate of CMV disease within the first year after transplantation. Twenty-seven recipients experienced a rejection episode, 14 of which had CMV disease, mostly after rejection, suggesting that in this group, CMV disease is not a risk factor for rejection. KIR gene or genotype distribution were similar between the CMV diseased and CMV disease-free group. Twenty-seven recipients (30%) carried KIR-AA genotype, of which nine (33%) had CMV disease. Of the remaining 63 (70%) recipients with KIR-BX genotype, 30 (48%) had CMV disease. There was no significant difference between the two genotype groups with regard to occurrence of CMV disease, although there was a trend toward a lower incidence of CMV disease in recipients carrying the KIR-AA genotype. For CMV disease, we found no significant risk associated with the number of activating or inhibitory KIRs. Neither was missing KIR ligands for the inhibitory KIRs (HLA-C1/C2/Bw4) in recipients associated with lower rates of CMV disease. Conclusion In CMV-negative recipients, genotypic analysis of KIR repertoire and HLA ligands does not provide risk factors for primary CMV disease after renal transplantation.